Abdominal distension in female patients with irritable bowel syndrome: exploration of possible mechanisms. Issue 6 (June 1991) - Maxton, D G; Martin, D F; Whorwell, P J; Godfrey, M
Abstract : Abdominal distension is a common but little understood symptom of the irritable bowel syndrome. The authenticity of the symptom was confirmed by appreciable increases in girth measurement during the day in 20 patients with the irritable bowel syndrome compared with 20 control subjects. Objective corroboration of this finding was shown in the group with the irritable bowel syndrome by a highly significant increase in lateral abdominal 'profile' on computed tomography. Previously postulated mechanisms for distension--namely, retention of gas, depression of the diaphragm, and excess lumbar lordosis--were excluded by the radiological findings. Voluntary protrusion of the abdomen produced a completely different pattern on computed tomography to that observed in the irritable bowel syndrome. These observations suggest that abdominal distension may be related to changes in motility or tone of gastrointestinal smooth muscle.